PERSPECTIVES OF WASTEWATER TREATMENT BY MICROALGAE AT AN AIRPORT - Pavliukh , Lesia (Science-based technologies, 2021)
Due to experimental studies the improved technology is the next stage after mechanical and biological treatment, i.e. additional wastewater treatment was proposed. The proposed advanced technology has significant advantages because it is cyclical and provides the possibility of producing biofuels from microalgae removed after the absorption of nutrients, as well as the production of biofertilizers from sludge.